Analisis Kesiapan Mahasiswa Pendidikan Guru Sekolah Dasar dalam Menghadapi Pendidikan di Era Society 5.0 - Putri, Fadila Manja; Antosa, Zariul; Munjiatun, Munjiatun (Asian Journal of Early Childhood and Elementary Education, 2023)
This research aims to describe the readiness of Elementary School Teacher Education students in facing education in the Society 5.0 era in terms of their 21st century skills. This research was carried out using a quantitative descriptive approach with survey methods. The data collection technique is through a questionnaire containing indicators of physical readiness, psychological readiness and material readiness which have been adapted to the concept of society 5.0 which includes 21st century skills, namely learning and innovation skills which include creative and innovative, critical thinking and problem solving, communication and collaboration. The population and sample in this research are elementary school teacher education students at the Faculty of Teacher Training and Education, Riau University who are still active in taking part in lectures, namely 77 students from the class of 2022 and 77 students from the class of 2023. The research will be carried out in the odd semester 2023/2024. The research results obtained a percentage of 76.4% for physical readiness, 79% for psychological readiness, and 78% for material readiness. All the indicators are categorized as ready so that it can be concluded that students of Elemntary School Teacher Education, Faculty of Teacher Training and Education, University of Riau class of 2022 and class of 2023 in facing education in the Society 5.0 era show the ready category.